Genetic Variation for Agronomic and Fiber Quality Traits in a Population Derived from High‐Quality Cotton Germplasm. Issue 4 (1st July 2016) - Campbell, B.T.; Greene, J.; Wu, J.; Jones, D.C.
Abstract : Genetic improvement of fiber quality is necessary to meet the requirements of processors and users of upland cotton ( Gossypium hirsutum L.) fiber. To foster genetic improvement of cotton fiber quality, adequate genetic variation for the quantitatively inherited physical properties of cotton is required. Additionally, knowledge of the genetic architecture of fiber quality is needed to design effective breeding strategies to further improve fiber quality. In this study, our objective was to estimate genetic variance components and predict genetic effects for agronomic and fiber quality traits in a population derived from four known genotypic sources of high fiber quality. The majority of genetic variation present in a half‐diallel population derived from these four sources of high fiber quality was due to additive effects. Predicted genetic effects demonstrated that one of the four parents, MD 15, provides a unique genetic source of high fiber quality alleles that behave additively.